2022
DOI: 10.3390/healthcare10020396
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nurses’ Grit on Nursing Job Performance and the Double Mediating Effect of Job Satisfaction and Organizational Commitment

Abstract: Nursing performance can be an evaluation indicator of hospitals. Therefore, improving it positively affects the development of nurses, patients, guardians, hospitals, and society. This descriptive correlational study was conducted to provide basic data necessary to improve nurses’ work performance by examining the effects of nurses’ grit on nursing job performance and mediating effects of job satisfaction and organizational commitment. The study participants were 186 nurses working at a university hospital in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…First, according to the results of this study, we found grit has an essential impact on job satisfaction among nurses in Southwest China, which agrees with previous studies showing that high grit could result in high job satisfaction ( Ko and Kim, 2019 ; Cho and Kim, 2022 ). As a result, while constantly striving to achieve their goals without giving up, individuals positively influence and increase their satisfaction.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…First, according to the results of this study, we found grit has an essential impact on job satisfaction among nurses in Southwest China, which agrees with previous studies showing that high grit could result in high job satisfaction ( Ko and Kim, 2019 ; Cho and Kim, 2022 ). As a result, while constantly striving to achieve their goals without giving up, individuals positively influence and increase their satisfaction.…”
Section: Discussionsupporting
confidence: 91%
“…Nurses with low job satisfaction are more motivated to leave the field ( Gebregziabher et al, 2020 ; Hu et al, 2022 ). Moreover, job satisfaction can directly and indirectly affect nursing quality ( Kiliç et al, 2022 ; Wang et al, 2022 ) and nursing performance ( Cho and Kim, 2022 ). High-quality care is usually associated with high levels of job satisfaction ( Dilmaghani et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…People with high grit levels are reported to experience better performance and health outcomes across disciplines, professions, and cultures (Datu, 2021). In nursing and medicine there has been considerable interest in grit and the positive role it likely plays in reducing burnout and turnover intention and improving performance and well‐being (Cho & Kim, 2022; Dam et al, 2019; Jeong et al, 2019; Jumat et al, 2020; Terry & Peck, 2020). Studies have also investigated the factors that may precede, mediate, or moderate higher levels of grit (Schimschal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%